Caribbean Report 17-02-1992 - Jarvis, Mike (anchor); Savarin, Charles (interviewee); Dupiton, Thomas Eddy (interviewee); Baptiste, Sandra (correspondent); Ramphal, Shridath (interviewee); Fraser, Tony (correspondent); Barsotti, Frank (interviewee); Mansoor, Michael (interviewee) (The British Broadcasting Corporation, 1992)
An ACP-EC meeting is held in the Dominican Republic, but there is dissappointment due to the absence of ousted Haitian President Jean Bertrand Aristide. The President of the Dominican Republic is called on to give a statement since Aristide was advised to stay away by officials of the Dominican Republic who said there was fear for his safety. A Barbadian diplomat express dissappointment with the state of affairs in the regional integration movement as Caribbean leaders prepare for an informal summit in Jamaica. Chairman of the West Indian Commission, Sir Shridath Ramphal gives an address to the parliament of the Netherland Antilles on the work of the Commission and on the progress of regional integration, and there is a severe cash shortage in the Trinidad and Tobago's commercial banking sector.
1. Headlines (00:00-00:31)
2. Report on the absence of ousted President Jean Bertrand Aristide from an ACP-EC meeting in the Dominican Republic. Hugh Crosskill reports from the meeting and on the disappointment of many European delegates on the absence of Aristide. Views are aired by Dominica's ambassador to Brussels, Charles Savarin and Haitian Senator Thomas Eddy Dupiton who is leading the unofficial Haitian delegation at the meeting (00:32-06:41)
3. Report on the preparation by Caribbean leaders for their informal summit in Jamaica, while Sandra Baptiste interviews Val McComie, a former Barbadian diplomat and Deputy secretary of the OAS, who speaks on his dissappoinment with the state of affairs in the regional integration movement (06:42-08:50)
4. Report on the address by Sir Shridath Ramphal, chairman of the West Indian Commmission, to the parliament of the Netherland Antilles on the work of the Commission and on the progress of regional integration (08:51-11:08)
Keywords: Aristide, Jean-Bertrand.; Haiti -- Foreign relations -- Dominican Republic.; Haiti -- Presidents.; Haiti--Politics and government.; Ramphal, S. S.; West Indian Commission.; Banks and banking -- Trinidad and Tobago.; Financial institutions -- Trinidad and Tobago.; Savarin, Charles.; Dupiton, Thomas Eddy.; Caribbean Integration.; Barsotti, Frank.; Mansoor, Michael.